Social Representations: disabled person in employment - MOKHTARI, Naima (Journal of Human Sciences, 2021)
In this article, we will address the issue of disability and employment. We will analyze the social representations are the colleagues of people with disabilities.To do this, we will conduct a field survey, within the private company Ramdy located at Bejaia in Algeria. Based on a qualitative method and technique of semi-directed interview.